Estimates of the Best $M$-Term Trigonometric Approximations of the Classes $L_{β, p}^{ψ}$ of Periodic Functions of Many Variables in the Space $L_q$ - Konsevich, N. M. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We obtain order estimates for the best trigonometric approximations of the classes $L_{β, p}^{ψ}$ of periodic functions of many variables in the space$L_q$ for $1 < p < q ≤ 2$ and $1 < q ≤ p < ∞$.